Surface oxygen vacancies promoted Pt nanoparticles on celery-like CeO2 nanofibers for enhanced sinter-resistance and catalytic performance. (December 2022) - Tang, M.; Liu, S.; Fu, W.; Wang, J.; Yin, K.; Zhu, M.; Tian, J.; Sun, Y.; Dai, Y.
Abstract: Supported metal nanoparticles hold great promise for heterogeneous catalysis but are greatly persecuted by the poor thermal stability upon high temperatures. In this work, we facilely synthesized intriguing celery-like CeO2 nanofibers with high surface areas and hierarchical pores and channels by single-spinneret electrospinning. The nanofibers were explored as reliable support for polyvinylpyrrolidone (PVP)-stabilized Pt nanoparticles, followed by activation at 350 °C in N2 to eliminate PVP stabilizer and generate sufficient surface oxygen vacancies. Therefore, the resultant Pt@CeO2 was endowed with enhanced metal−support interaction and thereby promoted sinter-resistance. In this case, the Pt@CeO2 exhibited over six times higher activity after aging at 600 °C toward the hydrogenation of p -nitrophenol than that of Pt PVP /CeO2 . Moreover, the thermal-stable Pt@CeO2 significantly decreased the activation energy of soot oxidation from 178.0 kJ/mol to 109.4 kJ/mol, due to the abundant oxygen vacancies, as well as the promoted solid–solid contact by the interconnected and celery-like CeO2 nanofibers. After such a sinter-promoting exothermic reaction, the supported Pt nanoparticles maintained a small size of 5.78 nm. This approach provides a facile method to prepare noble metal catalysts with both high atom economy and sinterresistance. Graphical abstract: Oxygen-vacancy-rich celery-like CeO2 nanofibers endowed supported Pt nanoparticles with boosted sinter resistance and catalytic performance by the optimized metal–support interaction. Image 1 Highlights: Stabilizing Pt nanoparticles by oxygen-vacancy-rich celery-like CeO2 nanofibers. Optimizing the interaction between metal and support by facile heat treatment. Boosting the activity of Pt@CeO2 toward both hydrogenation and soot oxidation.